DIGITAL INTERPERSONAL COMMUNICATION: A STUDY OF HELP TALK PATTERNS IN THE PETANI HAY DAY COMMUNITY ON PLATFORM X - Khais Salman; Rizki Briandana (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2026)
This study examines digital interpersonal communication through help talk practices within the Petani Hay Day community on Platform X. The increasing use of social media has encouraged the formation of virtual communities where members exchange information, provide assistance, and build social relationships through computer-mediated communication (CMC). This research adopts an interpretive paradigm with a qualitative approach using netnography to explore communication patterns among community members. Data were collected from posts and replies within the community that demonstrate help-seeking, help-giving, and help-sharing interactions. The findings reveal that help talk functions as the dominant interaction pattern that structures communication within the community. The communication process forms a circular interaction pattern characterized by responsive feedback among members. In addition, help talk reflects various forms of supportive communication including emotional support, instrumental support, informational support, appraisal support, and network support. These findings demonstrate that digital interpersonal communication within virtual gaming communities can foster collaboration, strengthen digital solidarity, and sustain active participation among members.